Internal consistency reliability and construct validity of the Astley–Francis Scale of Attitude toward Theistic Faith among religiously unaffiliated, Christian, and Muslim youth in the UK. Issue 5 (27th May 2016) - Francis, Leslie J.; Lewis, Christopher Alan
ABSTRACT: The Astley–Francis Scale of Attitude toward Theistic Faith was designed to access the attitudinal dimension of religion across the major theistic faith traditions. This study examined the psychometric properties of the Astley–Francis Scale of Attitude toward Theistic Faith among a sample of 10, 678 13- to 15-year-old students from across the UK, exploring the performance of the scale independently among three groups: religiously unaffiliated students ( N  = 3711), Christian students ( N  = 6649), and Muslim students ( N  = 318). The data support the internal consistency reliability and the construct validity of this instrument among all three groups and commend it for application in further studies.